Romanticism and Rebellion: Coleridge’s Poetic Resistance to the Enlightenment through The Rime of the Ancient Mariner - Pratiwi, Dyani Prades; Qarimah, Aryana Nurul (Andalas International Journal of Socio-Humanities, 2025)
This research aims to see the romanticism contained in the poem and uses descriptive qualitative as the method. The results of this research are characteristics from the romantic era, which are nature, freedom, supernatural, and gothic. The choice of supernatural and gothic themes came from Coleridge's childhood memories of folk oral traditions as a child; "Gothic Ballads." Childhood memories were also chosen because of the saturation at that time, which only discussed something empirical and did not believe in something that could not be proven. This poem shows that the world as a strange experience is an important relationship between humans and their feelings. It offers the spirit and soul as weapons against the Enlightenment era, which is full of science and rationalism. This poem becomes one of the ways to express the freedom of thought. This spirit also makes “Lyrical Ballads” as the opening door of the romantic era.